2017
DOI: 10.1111/aji.12703
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G is increasingly expressed on the human uterine cervical intraepithelial neoplasia along with disease progression

Abstract: These findings indicate that A3G is associated with CIN, suggesting its important roles in human papillomavirus-induced pathophysiological processes such as CIN progression and viral elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Next, the healthy growing follicles and corpora lutea were independently evaluated under a microscope by 3 gynecologic endocrinologists (14) without any information about the origin of each slide (Figure 2B and C), and then their numbers were finally determined (Figure 2A, asterisks). If the judgment of health conditions differed, the less favorable evaluation was selected, as reported previously (15, 16).…”
Section: Methodsmentioning
confidence: 99%
“…Next, the healthy growing follicles and corpora lutea were independently evaluated under a microscope by 3 gynecologic endocrinologists (14) without any information about the origin of each slide (Figure 2B and C), and then their numbers were finally determined (Figure 2A, asterisks). If the judgment of health conditions differed, the less favorable evaluation was selected, as reported previously (15, 16).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, almost all cervical cancers and a significant fraction of head and neck cancers (HNSCC), all harboring frequent A3-related mutations, are associated with viral infections ( Vartanian et al, 2008 ; Lawrence et al, 2013 ). Additionally, A3G expression in HPV-induced uterine cervical intraepithelial neoplasia (CIN) and infiltration of A3G expressing CD3 positive T cells in CIN lesions were reported ( Iizuka et al, 2017 ). In contrast, the frequent occurrence of a characteristic mutational A3 signature ( Lawrence et al, 2013 ) in urothelial carcinoma (UC) is puzzling, as these tumors are thought to be caused predominantly by chemical carcinogens rather than viral infections ( Tolstov et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IFN-γ is assumed to be intimately associated with the elimination stage of the immunoediting paradigm [29]. It was reported that IFNs can induce A3G expression on the uterine cervical squamous cells [9]. In this study, A3G was found to participate in the interferon-alpha response and interferon-gamma response in SKCM patients, which might provide novel clues for SKCM treatments.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, the dysregulation of A3G is also involved in multiple tumorigeneses. For example, Takashi Iizuka et al found that A3G is closely correlated with uterine cervical intraepithelial neoplasia (CIN) and might become an effective biomarker to assess CIN progression [9]. Also, A3G was observed to drive tumorigenesis in hepatocellular carcinoma (HCC) and might mediate host innate resistance to HBV infection and HCC [10].…”
Section: Ivyspringmentioning
confidence: 99%